Thermo-poroelasticity and geomechanics - Selvadurai, A. P. S. (Cambridge University Press, 2017)
Investigations of multi-physical processes in geomaterials have gained increasing attention due to the ongoing interest in solving complex geoenvironmental problems. This book provides a comprehensive exposition of the classical theory of thermo-poroelasticity, complemented by complete examples to problems in thermo-poromechanics that are used to validate computational results from multi-physics codes used in practice. The methodologies offer an insight into real-life problems related to modern environmental geosciences, including nuclear waste management, geologic sequestration of greenhouse gases to mitigate climate change, and the impact of energy resources recovery on groundwater resources. A strong focus is placed on analytical approaches to benchmark the accuracy of the computational approaches that are ultimately used in real-life problems. The extensive coverage of both theory and applications in thermo-poroelasticity and geomechanics provides a unified presentation of the topics, making this an accessible and invaluable resource for researchers, students or practitioners in the field.